Social comparison relationship with self-love in adolescents and the implications of guidance and counselling - Rully, Miranda Firdika; Harahap, Ade Chita Putri; Rusman, Abdul Aziz (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
Confidence is one of the keys to someone being able to perform optimally in everything he does. Reaching that level of self-confidence requires maximum self-management. The purpose of this study was to find out how much social comparison affection is on self-love in adolescents at SMA Negeri 1 Bandar Khalipah. In this study, quantitative research methods and data analysis techniques used simple linear regression. The population of this study were 120 class XI students of SMA Negeri 1 Bandar Khalipah. The sampling technique used random sampling. The sample in this study was 120. The results of this study showed a relationship between social comparison and adolescent self-love, besides that, there was a significant relationship between perception and students' attitudes towards guidance and counselling with students' interest in utilizing guidance and counselling services.